Lavandula stoechas (L) a Very Potent Antioxidant Attenuates Dementia in Scopolamine Induced Memory Deficit Mice - Mushtaq, Aamir; Anwar, Rukhsana; Ahmad, Mobasher (Frontiers in Pharmacology, 2018)
The objective of the current project was to explore the pharmacotherapeutic role of Lavandula stoechas (L) for the management of dementia. Dementia is considered a global challenge of current century seeking special attention of pharmacologists to explore its best remedies. Methanolic extract of aerial parts of L. stoechas was tested for phytochemical analysis along with free radical scavenging activity. Behavioral studies were performed on scopolamine induced amnesic mice by using elevated plus maze (EPM), light and dark test and hole board paradigms. Biochemical investigations were made after decapitating the mice. Their brains were isolated for biochemical estimation of acetylcholinesterase (AChE), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH). Phytochemical study ensured the presence of total phenolic contents (285.91 ± 0.75 mg of GAE/g of extract), total flavonoids (134.06 ± 0.63 mg of RE/g of extract), total tannins (149.60 ± 0.93 mg of TAE/g of extract) and free radical scavenging activity (IC50 value = 76.73 µg/ml found by DPPH method). Behavioral studies indicated that animals of GVII showed higher inflexion ratio (0.40 ± 0.03) for EPM, spent most of time (227.17 ± 2.13 sec) in dark area of light dark test and had many hole pockings (39.83 ± 1.88) for hole board paradigm. Moreover, biochemical studies revealed that methanolic extract of L. stoechas (800 mg/Kg/p.o) significantly (P < 0.001) reduced brain AChE and MDA levels while improved SOD, CAT and GSH levels. Thus the findings suggest that L. stoechas stabilizes memory by enhancing cholinergic neurotransmission and by providing defense against oxidative stress in mice brain.